Klasifikasi Kepuasan Siswa Terhadap Kinerja Guru Smk Satrya Budi 2 Perdagangan Menggunakan Algoritma C4.5 - Kusuma, Wili Darma; Suhada, Suhada; Saifullah, Saifullah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The purpose of this study was to measure student satisfaction with teacher performance Smk Satrya Budi 2 Perdagangan using classification data mining techniques C4.5 Algorithm. Data Sources obtained from questionnaires that have been given to students Smk Satya Budi 2 Perdagangan and giving questionnaires to students as many as 97 students. attributes used as a parameter for assessing student satisfaction include: Teacher attendance (C1), Material Mastery (C2), Material Explanation (C3), Tasks (C4), Attitude Teacher (C5), and Teacher appearance (C6). The results of processing the C4.5 algorithm using the help of Weka software are the attributes of teacher attendance (C1) and material explanation (C3) which are attributes that affect student satisfaction on teacher performance. And the accuracy value shown against the suitability of the C4.5 algorithm with student satisfaction with teacher performance is 94%. The benefit of this research is to improve the quality of teacher performance and improve the quality of teacher teaching